The Effects of Gender Differences in the Kurdish Individual's Vision of Human Values in Kurdish Proverbs and its Dimensions Among University Students - A Cognitive Study – (Raparin Journal of Humanities (RJH), 2021)
The research has a variety of aims. First, to clarify the cognitive level of the Kurdish individual about human values ​​in Kurdish proverbs and its related dimensions, as well as to know the impact of gender differences on Kurdish proverbs and its dimensions. To achieve these two aims, 150 undergraduate university students participated randomly in the current research. The researchers used a self-designed data-gathering tool consisting of 204 varieties of Kurdish proverbs, each proverb with five Likert options. The psychometric of collection tool which is the validity and reliability of the instrument was measured and was at the required level and good enough to be used. In order to analyze the data of the research, the researchers used the (SPSS) statistical package for the social sciences program. After analyzing the data, the results of the research showed that the cognitive level of the Kurdish individual about human values ​​was at a high and positive level according to the five Likert options, and the effect of gender differences on human values ​​and their dimensions were not statistically significant except for four dimensions. The analysis also showed controversial results for negative proverbs about each gender variable. In conclusion, the study in light of the research results made some recommendations and scientific suggestions to the related field.